Investigating a severe acute malnutrition outbreak in Dubti District, Awsiresu Zone, Afar Region, Northeast Ethiopia (2022) - Abiyie Demelash Gashe; Dawit Zenebe Woldemichael; Fentahun Agegnehu Worku; Kedir Ali Mahmud; Aman Yesuf Endries (Frontiers Media S.A., 2024)
IntroductionEthiopia is a global hotspot for child malnutrition, with an estimated 1.2 million children under five affected by severe acute malnutrition (SAM) in 2022. In response, the country has integrated SAM into its broader disease surveillance system. In January 2022, the Dubti District Health Office in the Afar Region detected an unusual surge in SAM cases through its surveillance system. This study aimed to assess the extent of the outbreak and identify the associated risk factors.MethodsWe conducted an unmatched case-control study involving 258 mother-child dyads from five affected kebeles in the Dubti District of the Afar Region Ethiopia. The descriptive study included all 442 SAM cases from the line list, while 86 cases and 168 controls were selected using a simple random sampling method for the analytic study. The data were entered into EpiData software (version 3.1) and analyzed using SPSS software (version 25.0). Binary logistic regression (LR) analysis was performed to identify risk factors for SAM. Statistically, the results were summarized using an adjusted odds ratio (AOR), 95% confidence intervals (CIs), and a p-value of <0.05.ResultsThe median age of the cases was 22 months, with an interquartile range of 12-34 months. A total of 39 deaths were reported, with a case fatality rate (CFR) of 8.82%. The identified SAM risk factors included households with more than five members (AOR = 3.341, 95% CI: 1.475-7.563), more than five under-five children (AOR = 4.442, 95% CI: 2.000-9.866), lack of vaccination (AOR = 3.641, 95% CI: 1.618-8.198), pneumonia (AOR = 5.61, 95% CI: 2.488-12.651), diarrhea (AOR = 4.68, 95% CI: 2.169-10.097), lack of access to sanitation and hygiene (AOR = 3.18, 95% CI: 1.462-6.934), and household food insecurity (AOR = 9.46, 95% CI: 2.095-42.712).ConclusionThe study revealed a significant outbreak of SAM, with a CFR of 8.82%. The outbreak was associated with factors such as large family sizes, having multiple under-five children, a lack of vaccination, pneumonia, and diarrhea. These findings emphasize the urgent need to safeguard essential child health services, water supply, sanitation and hygiene, and household food security.